The THE EFFECT OF PRODUCT REVIEWS AND RATINGS ON CONSUMER PURCHASE DECISIONS ON THE SHOPEE MARKETPLACE: THE EFFECT OF PRODUCT REVIEWS AND RATINGS ON CONSUMER PURCHASE DECISIONS ON THE SHOPEE MARKETPLACE - Sharen Octavia; Neviyani; Shendy Andrie Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the influence of product reviews and ratings on consumer purchasing decisions on the Shopee platform in Jember. Using a quantitative approach, an online survey was conducted on 100 randomly selected partisipants, and the data was analyzed using multiple linear regression through SPSS. The analysis results indicate that product reviews have a positive and significant influence on purchasing decisions (β = 0.361; p < 0.01), while ratings have a greater influence (β = 0.613; p < 0.01). The F-test indicates that both variables simultaneously influence purchasing decisions (F = 85.885; p < 0.001), with an Adjusted R² of 0.632, meaning that 63.2% of the variation in purchasing decisions can be explained by reviews and ratings. These findings suggest that sellers should focus on improving product and service quality and optimizing the review system to enhance online reputation and consumer shopping experience. Keywords: Product Reviews, Ratings, Purchase Decisions, Marketplace, Shopee